ANALISIS WACANA KRITIS IKLAN OPERATOR SELULER (Teks dan Konteks Iklan XL dengan Kartu As) - Wicaksono, Andri (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2019)
This study aims to describe the form of word choice, cohesion and coherence as well as the grammatical elements that appear in the mobile operator's advertising discourse (Kartu As vs XL) and contextual meaning contained in the choice of Indonesian language ad words in mobile operator ads (Kartu As vs XL). Based on the analysis that has been done that the form of word choice, cohesion and coherence as well as the grammatical elements that appear in the discourse of advertisement of cellular operator (Kartu As vs XL) is including non-standard. Contextual meaning contained in the word choice discourse Indonesian language ads in the ad mobile carriers (Kartu As vs XL). Language expressed in the slogan service provider or choice of words used by the mobile operator service providers have meaning to be conveyed reflect the character of each enterprise mobile operator services.